PENGARUH KETERAMPILAN SOSIAL TERHADAP KEDISIPLINAN ANAK USIA DINI - Hisham Abd Malik (stit-islamic-village, 2021)
The aim of the research was to know the effect of social skills on early childhood discipline at TKIT Insan Ekselensia Jatiranggon. The research sample used was 40 students who were determined based on the cluster sampling technique. The data analyzed in this research is descriptive analysis and infrensial analysis. The results of the study show that the social skills possessed by a child affect their discipline, this is evidenced by the coefficient of determination (R-Square) = 0.265, this indicates that 26% of the variation in the discipline variable can be influenced by Social Skills.